The importance and promise of integrating Indigenous knowledges in nursing education - Vanessa Van Bewer; Roberta L. Woodgate; Donna Martin; Frank Deer (York University Libraries, 2020)
This paper explores the relevance of Indigenous perspectives within the nursing profession, and the importance of weaving these perspectives into nursing education. We suggest that Indigenous perspectives can support nursing's core ethical values of relationality and holism and may hold representational and transformational possibilities for students and educators alike. Guided by principles of Indigenous learning, we provide several exemplars from Canadian schools of nursing that have already begun the process of decolonizing their programs. We conclude by describing some of the challenges and considerations that may arise when Indigenous perspectives and approaches are considered for inclusion into nursing education programs.